Seismic Behaviour of Reinforced-Masonry Aggregate Under Different Types of Interaction Between Adjacent Dwellings - Saavedra-Flores, E; Torres-Olivares, S (Springer Science and Business Media B.V., 2024)
Assessing the seismic vulnerability of existing buildings is an essential task for the management of earthquake disasters. For this purpose, the seismic behaviour of buildings is usually determined under the assumption of isolated conditions, although aggregate structures are one of the most common typologies found in urban centres. This study aims to investigate the nonlinear static behaviour of aggregate dwellings consisting of grouted reinforced concrete block configurations commonly observed in San José, Costa Rica. This research investigates the use of several strategies to model connections between adjacent buildings which are typically found in modern building practises in this country. The methodology used here to analyse the seismic behaviour of isolated and row-aggregated dwellings reveals significant differences in their response under seismic loads, especially when acting perpendicular to the aggregate. The study reveals that the type of interaction considered between adjacent buildings has a very important impact on the seismic capacity and failure mechanisms of the aggregated structures. This procedure can also be applied to the vulnerability assessment and retrofit of existing aggregates. © The Author(s) 2023.